51.1k views
3 votes
15h - 13h - h + 3= 7

User AlexHalkin
by
4.6k points

1 Answer

0 votes

Answer:


h=4

Step-by-step explanation: We need to solve for h in the given equation, which is:


15h-13h-h+3=7

Isolating unknowns and constants:


\begin{gathered} 15h-13h-h+3=7\rightarrow15h-14h+3=7 \\ \therefore\rightarrow \\ 15h-14h=7-3=4 \\ \therefore\rightarrow \\ 15h-14h=4 \end{gathered}

Simplifying gives:


\begin{gathered} 15h-14h=4 \\ \therefore\rightarrow \\ h=4 \end{gathered}

User Texnic
by
5.7k points